SM Social Media as a Tool for English Language Learning Among Junior High School Students - Simanungkalit, Ate Gueen; Bane, Elvi Rianti (DIDASCO, 2025)
This study explores the use of social media in learning English among junior high school students. The research was conducted at a private junior high school, involving 81 respondents from grades 7A, 7C, and 7D. A quantitative research method was employed, utilizing a questionnaire as the primary data collection instrument. The collected data were analyzed using descriptive statistical analysis. The results indicated a very high level of social media usage for learning English among the students, with a mean score of 4.27. This suggests that respondents frequently utilize social media platforms for English language acquisition. Based on the findings, it is recommended to leverage social media in English instruction, as students are highly engaged with these platforms, which can attract their interest and motivation. However, the study also identified challenges, such as potential distractions, exposure to inaccurate language content, and a lack of guidance from teachers. Keywords -- social media, learning English, Technology Acceptance Model, junior high school, digital learning   Penelitian ini menelusuri penggunaan media sosial dalam pembelajaran bahasa Inggris di kalangan siswa SMP. Penelitian ini dilakukan di SMP swasta, melibatkan 81 responden dari kelas 7A, 7C, dan 7D. Metode penelitian kuantitatif digunakan, dengan kuesioner sebagai instrumen pengumpulan data utama. Data yang terkumpul dianalisis menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan tingkat penggunaan media sosial yang sangat tinggi untuk pembelajaran bahasa Inggris di kalangan siswa, dengan skor rata-rata 4,27. Hal ini menunjukkan bahwa responden sering menggunakan platform media sosial untuk pemerolehan bahasa Inggris. Berdasarkan temuan ini, disarankan untuk memanfaatkan media sosial dalam pembelajaran bahasa Inggris, karena siswa sangat terlibat dengan platform ini, yang dapat menarik minat dan motivasi mereka. Namun, studi ini juga mengidentifikasi tantangan, seperti potensi gangguan, paparan konten bahasa yang tidak akurat, dan kurangnya bimbingan dari guru.   Kata kunci — media sosial, pembelajaran bahasa Inggris, Model Penerimaan Teknologi, SMP, pembelajaran digital